2000
DOI: 10.1097/00007632-200008150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Lumbar Supports

Abstract: There is evidence that lumbar supports reduce trunk motion for flexion-extension and lateral bending. More research is needed on the separate outcome measures for trunk motion before definite conclusions can be drawn about the work conditions in which lumbar supports may be most effective. Studies of trunk motion at the workplace or during specified lifting tasks would be especially useful in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
82
0
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 48 publications
(80 reference statements)
3
82
0
7
Order By: Relevance
“…On the other hand, it has been reported that lumbar supports have no effect on decreasing myoelectrical activities in the erector spinae muscle 3) . In general, wearing a lumbar support for a long period of time only promotes disuse atrophy of the trunk muscles and is, therefore, not preferable 1) .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, it has been reported that lumbar supports have no effect on decreasing myoelectrical activities in the erector spinae muscle 3) . In general, wearing a lumbar support for a long period of time only promotes disuse atrophy of the trunk muscles and is, therefore, not preferable 1) .…”
mentioning
confidence: 94%
“…Biomechanical studies have revealed that lumbar supports have the following effects : (1) they support the back so that it cannot be bent too much when lifting a large object 2) ; (2) they restrict flexion -extension and side flexion of the trunk, but not rotation 3) ; (3) they reduce intra -discal pressure of the lumber vertebrae 4) ; and (4) they increase erector spinae muscle pressure, but not intraabdominal pressure 5) . On the other hand, it has been reported that lumbar supports have no effect on decreasing myoelectrical activities in the erector spinae muscle 3) .…”
mentioning
confidence: 99%
“…Various conservative treatments are conducted for LBP, including lumbar support braces that can be used for LBP treatment as well as injury prevention 1 -6) . In general, the effects of these braces results from both the restriction of flexion -extension movements and lateral bending 7) as well as the reduction of intradiscal pressure on the lumbar vertebrae 8) and the decrease of load on the trunk 9) . However, in spite of the popularity of these supports and the availability of various designs, there is insufficient evidence regarding their effectiveness 2,6) .…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of the popularity of these supports and the availability of various designs, there is insufficient evidence regarding their effectiveness 2,6) . In addtion, the relationsship between muscle fatigue, muscle activity and low back pain remain an unresolved conrtaversial issue, and a causal relationship between muscle fatigue and Correspondence author : Miho Sekiguchi, MD, PhD E -mail : miho -s@fmu.ac.jp https://www.jstage.jst.go.jp/browse/fms http://www.fmu.ac.jp/home/lib/F -igaku/ 142 H. SAITO et al low back pain have not been found 7) . Furthermore, the effectivness of lumbar support treatment on back muscles has yet to be fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Different chair designs have emerged aimed at allowing the individual to assume a correct seating posture while maintaining comfort and functionality 13,14) . Numerous studies have investigated the impact of chair design parameters and the position of VDTs on neck, shoulder, and back pain, including the backrest type 13) , and the associated physiological responses, subjective discomfort ratings, and user perceptions [15][16][17][18] . Among the various factors in seating and chair design, the backrest has become a focal point 19) .…”
mentioning
confidence: 99%